New insights on the phytochemical intervention for the treatment of neuropsychiatric disorders using the leaves of Michelia champaca: an in vivo and in silico approach - Pushpa V. H.; Jayanthi M. K.; Rashmi H. R.; Veeresh Kumar N. Shivamurthy; Shashank M. Patil; Prithvi S. Shirahatti; Ramith Ramu (Taylor & Francis Group, 2022)
Context Michelia champaca L. (Magnoliaceae) has been known since ancient times for its rich medicinal properties.Objective The ethanol extract of Michelia champaca leaves (EEMC) was evaluated on depression and anxiety using in vivo and in silico studiesMaterials and methods Swiss albino mice were divided into control, standard, 100 and 200 mg/kg b.w. EEMC groups and for drug administration using oral gavage. The antidepressant activity was evaluated using forced swim test (FST) and tail suspension test (TST) whereas the anxiolytic activity through elevated plus maze and light and dark tests. The in silico studies included molecular docking against human potassium channel KCSA-FAB and human serotonin transporter, and ADME/T analysis.Results Open arm duration and entries were comparable between 200 mg/kg b.w. group (184.45 ± 1.00 s and 6.25 ± 1.11, respectively) and that of diazepam treated group (180.02 s ± 0.40 and 6.10 ± 0.05, respectively). Time spent in the light cubicle was higher (46.86 ± 0.03%), similar to that of diazepam (44.33 ± 0.64%), suggesting its potent anxiolytic activity. A delayed onset of immobility and lowered immobility time was seen at both the treatment doses (FST: 93.7 ± 1.70 and 89.1 ± 0.40 s; TST: 35.05 ± 2.75 and 38.50 ± 4.10 s) and the standard drug imipramine (FST: 72.7 ± 3.72 and TST: 30.01 ± 2.99 s), indicative of its antidepressant ability. In silico studies predicted doripenem to induce anxiolytic and antidepressant activity by inhibiting human potassium channel KCSA-FAB and human serotonin transporter proteins, respectively.Conclusions EEMC is a rich source of bioactive compounds with strong antidepressant and anxiolytic properties.